Respuesta :
a = 99 and b = 67
Step-by-step explanation:
Let the 2 numbers be a , b
Sum is 166
[tex]a + b = 166 \\ \\ b = 166 − a \: \: \: \: ....(i)[/tex]
Difference is 32
[tex]a - b = 32 \\ \\ a - ( 166 - a ) = 32 \\ \\ a - 166 + a = 32 \\ \\ 2a = 32 + 166 \\ \\ 2a = 198 \\ \\ a = \frac{198}{2} \\ \\ a = 99.[/tex]
put a = 99 in eq (i)
[tex]b = 166 - a \\ \\ b = 166 - 99 \\ \\ b = 67.[/tex]
Answer: 99, 67
Step-by-Step Explanation:
Let the Larger Number be ‘a’
Let the Smaller Number be ‘b’
Sum = 166
Difference = 32
Therefore,
=> a + b = 166 (Eq. 1)
=> a - b = 32 (Eq. 2)
Adding Eq. 1 and 2, we get :-
2a = 198
a = 198/2
=> a = 99
Substitute value of ‘a’ in Eq. 2 :-
a - b = 32
(99) - b = 32
99 - b = 32
99 = 32 + b
99 - 32 = b
b = 99 - 32
=> b = 67
Therefore,
Larger Number: a => 99
Smaller Number: b => 67
Step-by-Step Explanation:
Let the Larger Number be ‘a’
Let the Smaller Number be ‘b’
Sum = 166
Difference = 32
Therefore,
=> a + b = 166 (Eq. 1)
=> a - b = 32 (Eq. 2)
Adding Eq. 1 and 2, we get :-
2a = 198
a = 198/2
=> a = 99
Substitute value of ‘a’ in Eq. 2 :-
a - b = 32
(99) - b = 32
99 - b = 32
99 = 32 + b
99 - 32 = b
b = 99 - 32
=> b = 67
Therefore,
Larger Number: a => 99
Smaller Number: b => 67